Aktivitas Antimikroba dan Antioksidan Jamur Laut yang Berasosiasi dengan Spons Pseudoceratina sp. dari Perairan Pantai Amed - Adi, I Made Agus Kusuma; Witantri, Ni Komang Diah Eka; Wulandari, Ni Made Widya; Leliqia, Ni Putu Eka; Wirajana, I Nengah; Wibowo, Joko Tri; Ware, Ismail; Ariantari, Ni Putu (Jurnal Ilmiah Medicamento, 2026)
Background: Marine fungi are organisms capable of growth and spore production in the marine environment and establishing symbiotic relationships with other marine organisms. Because of their high biochemical diversity, marine fungi are considered a potential source for the discovery of new natural compounds with various biological activities.Objective: This study aims to conduct molecular identification and assess the bioactivity potential of the methanol extract obtained from endophytic fungi associated with the marine sponge Pseudoceratina sp. from the Amed Coastal Waters, Bali.Methods: Eight marine fungi were isolated in this study and identified through molecular biology protocol as Aspergillus tamarii SP-3-1-4, Aspergillus nomiae SP-3-2 (A), Penicillium citrinum SP-3-2-1, Aspergillus protuberus SP-3-2-3, Aspergillus sydowii SP-3-2-4, Aspergillus sydowii RM NS SP-3B, Aspergillus clavatonanicus RM NS SP-3-2 A, and Aspergillus nomiae RM NS SP-3-2 B. The fungi were subsequently fermented on rice media containing salt and/or without salt. In the final stage of fermentation, secondary metabolites were extracted using ethyl acetate, followed by liquid-liquid extraction using methanol containing 10% water and n-hexane. The resulting methanolic extracts were subjected to phytochemical analysis and bioassays.Results: The phytochemical screening results of the methanol extracts showed that all extracts contained alkaloids. Among the tested extracts, the extract obtained from the fermentation of the fungus A. protuberus SP-3-2-3 on rice medium with the addition of salt showed the highest activity against Methicillin-resistant Staphylococcus aureus ATCC 3351 with an inhibition zone diameter of 7.99±0.20 mm. The fungus A. sydowii SP-3-2-4 cultured with and without salt in rice media exhibited the most potent antioxidant capacity, with IC50 values of 37.02±1.12 and 32.48±0.81 µg/mL. Conversely, A. nomiae SP-3-2 (A), fermented without salt, displayed the highest toxicity with an LC50 value of 0.88±0.69 µg/mL.Conclusion: Based on the pharmacological potential of extracts produced by the marine fungi associated with the sponge Pseudoceratina sp. found in the present study, identification of bioactive secondary metabolites and their mode of action is propitious for further investigation.